2016
DOI: 10.1016/bs.enz.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The Many Roles of PCNA in Eukaryotic DNA Replication

Abstract: Proliferating cell nuclear antigen (PCNA) plays critical roles in many aspects of DNA replication and replication-associated processes, including translesion synthesis, error-free damage bypass, break-induced replication, mismatch repair, and chromatin assembly. Since its discovery, our view of PCNA has evolved from a replication accessory factor to the hub protein in a large protein-protein interaction network that organizes and orchestrates many of the key events at the replication fork. We begin this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
174
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(197 citation statements)
references
References 127 publications
(134 reference statements)
13
174
0
10
Order By: Relevance
“…We constructed a double EhDNAligI‐Phe11Ala:Phe12Ala mutant aimed to eliminate the aromatic residues of the PIP box 3 10 α‐helix without completely eliminating its secondary structure 36, 37. We found that the enzymatic activity of EhDNAligI‐Phe11Ala:Phe12Ala mutant is simulated 9.8‐fold by wild‐type EhPCNA, supporting our previous results that the PIP box interaction is not necessary for nick‐sealing stimulation.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…We constructed a double EhDNAligI‐Phe11Ala:Phe12Ala mutant aimed to eliminate the aromatic residues of the PIP box 3 10 α‐helix without completely eliminating its secondary structure 36, 37. We found that the enzymatic activity of EhDNAligI‐Phe11Ala:Phe12Ala mutant is simulated 9.8‐fold by wild‐type EhPCNA, supporting our previous results that the PIP box interaction is not necessary for nick‐sealing stimulation.…”
Section: Resultssupporting
confidence: 82%
“…Because of the lack of stimulation of EhDNAlig by EhPCNA mutants, we were curious to test if EhDNAlig mutants that replace the most prominent hydrophobic interactions of the PIP box in EhDNAligI with EhPCNA would have an effect on nick-sealing activity upon incubation with wild-type and mutant forms of EhPCNA. We constructed a double EhDNAligI-Phe11Ala:Phe12Ala mutant aimed to eliminate the aromatic residues of the PIP box 3 10 a-helix without completely eliminating its secondary structure [36,37]. We found that the enzymatic activity of EhDNAligI-Phe11Ala:Phe12Ala mutant is simulated 9.8-fold by wild-type EhPCNA, supporting our previous results that the PIP box interaction is not necessary for nicksealing stimulation.…”
Section: Exonuclease Footprinting Indicates That Ehpcna Binds To Ehdnsupporting
confidence: 82%
“…PCNA is a ring-shaped homotrimer that encircles the DNA (Figure 1), hence it is also referred to as a sliding clamp (Boehm et al, 2016a; Dieckman et al, 2012; Moldovan et al, 2007; Warbrick, 2000). PCNA has a highly conserved six-fold symmetry since each of the monomers are composed of two similarly folded globular regions united by a flexible interdomain connecting loop (IDCL).…”
Section: General Structural and Functional Characteristics Of Pcnamentioning
confidence: 99%
“…This is a potentially attractive target due to its different expression profile in healthy proliferating cells vs. cancer cells. In healthy cells, PCNA appears to be expressed in the nucleus and is involved in DNA replication and repair (295), whereas in cancer cells, it is overexpressed on the cell surface (296). By constructing a monoclonal antibody against PCNA (14-25-9), the Porgador group was able to demonstrate that blocking this tumor antigen unleashes NK cell activity in-vitro and in-vivo, and promotes tumor clearance in murine xenograft models of autologous HNSCC patient NK cells (294).…”
Section: Novel Nk Cell Inhibitory Checkpoints/tumor Antigens For Blocmentioning
confidence: 99%